CINEMATIC INFLUENCES IN GENDER DISCOURSE: A QUEER DISCOURSE ANALYSIS OF SELECTED MANUEL PUIG’S NOVELS - Casibual, Joseph Padios (Sanata Dharma University, 2023)
The connection between mass culture and literature has grown extensively over the years. This is evident in the works of Manuel Puig, whose regard for popular culture, particularly films, is undeniable. He cinematically appropriates his characters, themes, narration, and plot making, such as the source text, instead of being the translated material. This paper is an exploration of gender politics and identity through the lens of the characters portrayed in the following texts: (1) Betrayed by Rita Hayworth (1968), (2) Heartbreak Tango (1996), (3) Kiss of a Spider Woman (1973), and Pubis Angelical (1979). The contention of this paper revolves around the influence of mass culture, particularly the role of films towards identity construction, specifically on gender-where issues like politics, patriarchy, and nationalism were taken into consideration. It is clear that the characters negotiated their identity through films which functioned as their threshold to consciousness, escape, and expression contrary to the society they’re living in. Furthermore, the themes reinforced the discourse of gender politics making the texts a tool for criticism towards the strict conventions imposed by the Boom period; making Puig’s writing a form of protest and a commentary on the issues relevant to the time and milieu the texts were written.